1969
DOI: 10.1161/01.res.24.3.303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enhanced Contractility on the Left Ventricular Response to Vagus Nerve Stimulation in Dogs

Abstract: In the canine isovolumetric left ventricle preparation, stimuli were applied to the efferent end of a transected cervical vagus nerve. The changes in left ventricular systolic pressure in response to vagal stimulation were compared under control conditions and when ventricular contractility was enhanced by various kinds of inotropic stimulation-left stellate ganglion stimulation, paired pacing, calcium chloride infusions, aminophylline infusions, and acetylstrophanthidin injections. Vagal stimulation under con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0
1

Year Published

1972
1972
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 23 publications
4
26
0
1
Order By: Relevance
“…The positive inotropic action of phenylephrine was also antagonized prominently by the same concentration of carbachol. The accentuated antagonism on the mammalian ventricular myocardium (16), as described usually for whole animal experiments (11)(12)(13)(14)(15) as well as in the isolated ventricular muscle (17), was confirmed to be operative also in the canine isolated ventricular muscle.…”
Section: Discussionmentioning
confidence: 80%
“…The positive inotropic action of phenylephrine was also antagonized prominently by the same concentration of carbachol. The accentuated antagonism on the mammalian ventricular myocardium (16), as described usually for whole animal experiments (11)(12)(13)(14)(15) as well as in the isolated ventricular muscle (17), was confirmed to be operative also in the canine isolated ventricular muscle.…”
Section: Discussionmentioning
confidence: 80%
“…It is well known that there may be significant sympathetic-parasympathetic interactions. These interactions may result in enhanced parasympathetic effects (17,22) during exercise and/or recovery, a phenomenon termed "accentuated antagonism" (17,19,20,25). Nevertheless, the physiology of interest is the parasympathetic effect that is noted during exercise and recovery, when there is enhanced sympathetic tone.…”
Section: Discussionmentioning
confidence: 99%
“…24 Vagal antagonistic action, by opposing sympathetic actions at both pre-and postjunctional levels, 25,26 exists not only in the chronotropic effect but also in the control of ventricular performance, intracellular calcium handling, and cardiac electrophysiology. 4,27,28 Schwartz et al 29 demonstrated in chloralose anesthetized cats that afferent vagus nerve stimulation (VNS) reflexively inhibited efferent sympathetic nerve activity. About 40 years later, using an implanted device to record autonomic nerve activity continuously in ambulatory canines, Shen et al 30 observed that chronic left-sided cervical VNS led to a significant reduction in sympathetic nerve activity from the left stellate ganglion (LSG).…”
Section: Autonomic Influences On Cardiac Electrophysiology Interplay mentioning
confidence: 99%